Effects of Torbangun Leaves(Coleus amboinicus Lour) Extract on Blood Glucose and Super Oxide Dismutase Activity in Hyperglycemic Rats - Andrestian, Meilla Dwi; Damanik, Muhammad Rizal Martua; Anwar, Faisal; Yuliana, Nancy Dewi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This research aimed to analyze the yield of torbangun extract, flavonoid content, and antioxidant activity of TE-S and its effect on the activity of SOD enzymes and blood glucose level in hyperglycemic rats as a DM animal model. The water content of simplicia was measured by the gravimetric method. The antioxidant activity of TE-S was determined using the DPPH method, while the total flavonoid was measured using spectrophotometry. The study was a completely randomized design using 25 Sprague Dawley rats. Rats were divided into four groups, namely NG (negative control, hyperglycemic rats), N (normal rats), H-IM (control of metformin drugs 62.5 mg/kg of BW), and H-IT (TE-S 620 mg/kg of BW). The treatment was carried out for 14 days. FBG levels were taken on day 0, 4, 7, 11, and 14, measured using a glucometer, while blood serum SOD levels were measured using ELISA. The study showed the water content of torbangun simplicia was 7.99% and TE-S yield from simplicia was 4.69%. TE-S contains total flavonoids of 3.91% and antioxidant activity (IC50) of 306.28 ppm with a standard of 1 ppm vitamin C. TE-S treatment significantly decreased FBG (p=0.005, α=0.01) and increased SOD levels in hyperglycemic rats. TE-S has the potential to increase blood serum SOD levels by contributing to the availability of antioxidants and decreasing blood glucose levels in hyperglycemic rats.